Pancytopenia Due to Vitamin B12 and Folic Acid Deficiency-A Case Report - Zoé Depuis; Sophie Gatineau-Sailliant; Olivier Ketelslegers; Jean-Marc Minon; Marie-Christine Seghaye; Myriam Vasbien; Marie-Françoise Dresse (MDPI AG, 2022)
We report a case of severe pancytopenia in a 15-year-old patient due to a severe deficiency in vitamin B12 and folic acid, probably of nutritional origin. The clinical and biological course was favorable after vitamin supplementation. With this case, we discuss the diagnostic approach of pancytopenia with megaloblastic anemia in children and adolescents, as well as the mechanisms involved in vitamin B12 and B9 deficiency. Hypovitaminosis B12 is known in its severe form but its diagnosis is often made difficult by insidious signs and symptoms. Traditional intramuscular replacement therapy has now proven to be effective orally. The clinical manifestations of folic acid deficiency are relatively similar to those of vitamin B12 deficiency, reflecting their intricate co-enzymatic functions. Its supplementation is administered orally.